К изучению энтомофауны песков Красноградского района Харьковской области - Мищенко, А.А. (Вестник зоологии, 1973)
The article deals with the results of studies in soil entomofauna of sands in flood plain benches and alluvial plain of the river Berestovaya in the Krasnograd district (Kharkov region) in the North of the steppe zone. 157 insect species from 8 orders were found, Coleoptera being predominant (130 species). Most found species are widely distributed but there is a considerable amount of steppe and Mediterranean species. Soil entomofauna of some biotopes is different: the fauna of the open sandy areas and glades in pine forests is the richest, the fauna sands near river-beds is the poorest. Many forests and field pests are registered, the following species being most dangerous: Melolontha melolontha L. , M. hippocastani F., Polyphylla fullo L., Anoxia pilosa F.